SOCIETY AND EDUCATION: THE EXPERIENCE OF IMPERIAL RUSSIA - A. L. Andreev (Высшее образование в России)
The article, in a comparative context, considers the features of the Russian model of education, and the role of education in the process of social evolution of Russia since Peter the Great’s reforms until 1917. The paper justifies the concept of advanced development of education. In Russia it acted as a main driving force of the country’s modernization. Particular attention is paid to the role of education in the transformation of the social structure of Russian society, including the formation of meritocratic elite of a modern type. Considering the sociocultural processes in the Russian society of the times of Alexander III and Nicholas II, the author draws attention to a new educational request from society and the educational boom that took place during this period. From his point of view, this educational boom served as a real beginning of the cultural revolution, which was then continued in the post-October period of Russia’ s history.